Biomechanical Properties of Suture Anchor Repair Compared With Transosseous Sutures in Patellar Tendon Ruptures: A Cadaveric Study. (November 2013) - Ettinger, Max; Dratzidis, Antonios; Hurschler, Christof; Brand, Stephan; Calliess, Tilman; Krettek, Christian; Jagodzinski, Michael; Petri, Maximilian
Background: Ruptures of the patellar tendon are debilitating injuries requiring surgical repair. Reliable data about the most appropriate suture technique and suture material are missing. The standard procedure consists of refixing the tendon with sutures in transpatellar tunnels, sometimes combined with augmentation. Hypothesis: Suture anchors provide at least equal results concerning gap formation during cyclic loading and ultimate failure load compared with transosseous suture repair. Study Design: Controlled laboratory study. Methods: A total of 30 human cadaveric patellar tendons underwent tenotomy followed by repair with 5.5-mm titanium suture anchors, 5.5-mm resorbable hydroxyapatite suture anchors, or transpatellar suture tunnels with No. 2 Ultrabraid and the Krackow whipstitch technique. Biomechanical analysis included pretensioning the constructs at 20 N for 30 seconds and then cyclic loading of 250 cycles between 20 and 100 N at 1 Hz in a servohydraulic testing machine with measurement of elongation. After this, ultimate failure load and failure mode analysis was performed. Results: Compared with transosseous sutures, tendon repairs with suture anchors yielded significantly less gap formation during cyclic loading ( P < .05) and resisted significantly higher ultimate failure loads ( P < .05). Common failure mode was pullout of the eyelet within the suture anchor in the hydroxyapatite anchor group and rupture of the suture in the titanium anchor group and—at lower load to failure—in the transosseous group. Conclusion: Patellar tendon repair with suture anchors yields significantly better biomechanical results than repair with the commonly applied transosseous sutures. Clinical Relevance: These findings may be of relevance for future clinical treatment of patellar tendon ruptures. Randomized controlled clinical trials comparing suture anchors to transosseous suture repair are desirable.